THE CORRELATION BETWEEN TYPE 2 DIABETES MELLITUS WITH BACTERIAL INFECTION IN COVID-19 PATIENTS ADMITTED TO INTENSIVE CARE UNIT AT CENTRAL GENERAL HOSPITAL PROF. DR. I.G.N.G. NGOERAH DENPASAR IN 2021-2022 - Bayu Saputra, Ida Bagus Prema Satia; Suranadi, I Wayan; Senapathi, Tjokorda Gde Agung (E-Jurnal Medika Udayana; Vol 13 No 2 (2024): E-Jurnal Medika Udayana, 2024)
Type 2 Diabetes Mellitus (T2DM) has a detrimental impact on the immune system, resulting in a decrease in the body's immune response, making patients highly susceptible to bacterial infections. Patients with T2DM, especially those treated in the Intensive Care Unit (ICU) of a hospital, face an increased risk of infection. The emergence of COVID-19, which also infects T2DM patients, further diminishes the immune system's function in these patients. Consequently, individuals with both T2DM and COVID-19 are at a heightened risk of developing secondary infections, commonly referred to as Hospital-Acquired Infections.This research aims to explore the relationship between T2DM, assessed through blood sugar levels, and the occurrence of bacterial infections in COVID-19 patients treated in the ICU of Prof. Dr. I.G.N.G. Ngoerah Central Hospital from 2021 to 2022. The research design employed is quantitative analytical correlational study using a cross-sectional approach, with a sample size of 98 patients collected from the Medical Records and Hospital Management System of Prof. Dr. I.G.N.G. Ngoerah Central Hospital in Denpasar. This study found that there is a significant correlation between patient’s infection profile with random blood glucose levels with an Odds Ratio (OR) of 1.15 (95% CI: 1.04 – 1.27; p = 0.013). Additionally, a significant relationship was observed between the severity of COVID-19 and bacterial infections in patients, with an Odds Ratio of 1.12 (95% CI: 1.01 – 1.26; p = 0.04). Keywords : T2DM, ICU, Hospital-Acquired Infection